Competence of Indonesian Courts in Adjudicating Divorce of Foreign Citizens - Inayatuzzahra, Inayatuzzahra; Rahma, Sahilda Lailatul; Lestari, Okti Indah; Muaviroh, Siti (JURNAL HUKUM SEHASEN, 2025)
The presence of foreign nationals who live in Indonesia in the long term raises various international legal issues, one of which is related to divorce between the spouses of foreign nationals married abroad. This article discusses the authority of Indonesian courts in adjudicating divorce cases between two foreign nationals married abroad, as well as the application of international civil law principles in determining applicable law. Using the example of the divorce case of a foreign national couple from the United States who married in Philadelphia and lived in Indonesia for more than seven years, this article outlines the application of principles such as lex loci celebrationis, lex domicilii, and lex rei sitae in determining the authority of the court and the applicable law. The analysis shows that Indonesian courts have the authority to adjudicate this divorce based on the spouse's long-standing residence in Indonesia and based on the principles of international civil law that avoid renvoi. Therefore, the Indonesian court can decide this divorce case even though the marriage took place abroad.